PERANAN KOPI RAKYAT TERHADAP PEREKONOMIAN WILAYAH KABUPATEN LAMPUNG BARAT - Lina Marlina; Arya Hadi Dharmawan; Yetti Lis Purnamadewi (Lampung University, 2017)
This study aims to analyze the value chain of coffee commodity, to review and to analyze the economic contribution of coffee to household incomes of coffee farmers and also to assess and to examine the role of coffee plantations sector in supporting the economy of West Lampung Regency. The experiment is conducted in June to July 2013 in Gedung Surian Sub-District, West Lampung Regency. The Respodent are coffee farmers, coffee traders, and women’s farming groups. Data analysis includes an economic analysis of coffee smallholders, marketing efficiency analysis and regional analysis. The results are: (1) Coffee commodity chain in the research area is quite long and complicated because the farmers faced many difficulties to sell their coffee directly so farmer as price taker. (2) Coffee sector contributes significantly to overall household income of coffee farmers. Farmers' share of household expenditure for non-food needs, especially tertiary is the highest. (3) Coffee deserves to be developed in West Lampung because it has rapid growth and competitive. Coffee plantation sector also employs more than 20% people and contributed 6,49% to GDP of West Lampung Regency. The existence of additional potential revenue is Rp287.168.700.000,- from the coffee if it was processed in West Lampung.Key words: economic analysis, coffee smallholders, regional economic, value chain